UNDERSTANDING WEIGHT MANAGEMENT AMONG POSTNATAL WOMEN: A QUALITATIVE EXPLORATION OF EXPERIENCES AND CHALLENGES - Siti Zuhaidah Shahadan,; Nur Nazifa Firzanah Rohaizy,; Mohamad Firdaus Mohamad Ismail, (Journal of Islamic, Social, Economics and Development, 2024)
Postnatal weight retention (PWR) is the change between pre-pregnancy weight and weight after birth. PWR is a risk factor for women of childbearing age to develop obesity. Studies have shown that women who gain weight after childbirth or who do not lose their pregnancy weight are less likely to drop the weight and more likely to suffer from serious health issues. Nonetheless, the prevalence of PWR and obesity among women has kept increasing. Hence, this study aims to explore the experience of postnatal women in Kuantan that shape their weight management behaviours. This study employed a qualitative research study. Nine participants were recruited using purposive and snowball sampling methods. A semi-structured interview was conducted to obtain data on the experience, perceived benefits and perceived barriers of weight management among postanal women in Kuantan. All findings were analyzed using thematic analysis. Three categories with nine themes were extracted from the data. The study identifies various factors such as kinship support, perceived benefits of losing weight (including nutritious eating habits, physical activity, and body appearance), people's opinions and perceived barriers (such as time constraints, commitment, and maladaptive eating behaviours) that influence postnatal women's ability to control their weight. In conclusion, this study highlights the importance of addressing postnatal weight retention (PWR) as a risk factor for obesity among women of childbearing age. These findings provide valuable insights for developing targeted interventions and support systems to help postnatal women manage their weight effectively and reduce the risk of obesity-related health issues.